Non-tariff measures in agriculture - Gourdon, Julien (OECD Publishing, 2020)
Sanitary and Phytosanitary (SPS) provisions and Technical Barriers to Trade (TBT) generally raise trade costs, but by providing a positive signal to consumers that enhances confidence in imported products they can also expand trade. This paper seeks to identify which specific elements of SPS and TBT measures are particularly trade enhancing. It investigates the trade cost and trade enhancing effects of SPS and TBT measures along with other types of NTMs in agricultural trade. It provides estimations on the quantity and price effects on 34 SPS and 24 TBT measures. The econometric results show that technical measures can increase import prices of agricultural products by nearly 15%, most of which comes from restriction or special authorisation for TBT or SPS reasons, such as registration requirements. Conformity assessment also tends to significantly increase the cost of trade. Trade enhancing effects are identified for labelling and packaging requirements, which are also the measures with relatively low associated trade costs
Keywords: Agriculture and Food